ISOLASI DAN IDENTIFIKASI GOLONGAN KIMIA AKTIF ANTIOKSIDAN EKSTRAK ETANOL DAUN JAMBU METE (Anacardium occidentale L.) - A Amaliah Dahlia; Hasnawati Hasnawati (Jurnal Fitofarmaka Indonesia, 2014)
Has been carried out isolation and identification of active chemical groups ethanol extract antioxidant Cashew Leaves (Anacardium occidentale L.) in aims is determine the class of the active antioxidant compounds from ethanol extract of Cashew Leaves (Anacardium occidentale L.). Sample of 400 grams of macerated with ethanol produces dry extract 20.087 grams. Dry done profile TLC plate and then eluted with eluent n-hexane: ethyl acetate (6:4), and then sprayed DPPH to determine antioxidant compounds. Ethanol extracts was than isolated using vacum liquid chromatography column with n-exane, eluent ratio of n-hexane: ethyl acetate (9:1,8:2,7:3, 6:4, 5:5, 4:6, 3: 7, 2:8, 1:9) and ethyl acetate. XI fractions obtained, then sprayed with DPPH fraction VI showed the most intense antioxidant activity. Results isolates obtained were then identified using uv-vis spectroscopy showed maximum absorption at a wavelength of 424.50 nm, Infrared spectroscopy showed absorbance at wave number 3393.18 cm-1 shows possibility the O-H group reinforced the wave number 1102.20 which indicates the possibility of a C-O group, te wave number 2923,44 cm-1 shows possibility the C-H (aromatic), the wave number 1555.13 cm-1 which indicates the possibility of a cluster C = C, as well as identification by using specific reagents. From the above observations indicate that isolates classes of flavonoids suspected.